Diagnostic ambiguity of aseptic necrobiosis of a uterine fibroid in a term pregnancy: a case report - Julius Sama Dohbit; Esther Ngo Um Meka; Joel Noutakdie Tochie; Igor Kamla; Celestin Danwang; Frank-Leonel Tianyi; Pascal Foumane; Gervais Ondobo Andze (BMC, 2019)
Abstract Background Uterine fibroids are the most common uterine tumours in females of reproductive age. During pregnancy, uterine fibroids may be complicated by aseptic necrobiosis. We herein report an ambiguous clinical presentation of uterine fibroids in pregnancy and discuss the diagnostic challenges encountered in our resource-constraint setting. Case presentation A term pregnant Cameroonian woman was admitted to our maternity unit with clinical findings suggestive of a strangulated umbilical hernia. She underwent an emergency caesarean section which fortuitously revealed aseptic necrobiosis of a uterine fibroid, managed within the same surgical intervention by myomectomy. Her post-operative course was uneventful. Conclusion The authors highlight the need for a high index of suspicion by healthcare providers, as well as the need for a multidisciplinary approach for a favourable maternal and foetal outcome.